2021
DOI: 10.1001/jamahealthforum.2021.3524
|View full text |Cite
|
Sign up to set email alerts
|

Practice Trends and Characteristics of US Hospitalists From 2012 to 2018

Abstract: This cohort study uses Medicare data to assess trends and characteristics among hospitalists who shift practice to settings outside of the hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 5 publications
2
8
0
Order By: Relevance
“…Other recent research suggests that between 2012 and 2018, nearly 25% of hospitalists first identified in 2012 shifted their full‐time practice to other settings while still doing part‐time hospitalist work 11 . Our data on PECOS‐identified hospitalists who no longer meet the 90% threshold seem to affirm that some hospitalists transition to nonhospital settings, such as skilled nursing facilities or office‐based settings.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Other recent research suggests that between 2012 and 2018, nearly 25% of hospitalists first identified in 2012 shifted their full‐time practice to other settings while still doing part‐time hospitalist work 11 . Our data on PECOS‐identified hospitalists who no longer meet the 90% threshold seem to affirm that some hospitalists transition to nonhospital settings, such as skilled nursing facilities or office‐based settings.…”
Section: Discussionsupporting
confidence: 53%
“…This requires further exploration. Third, hospitalists may be increasingly engaged in nonclinical work, such as quality improvement and administrative tasks, requiring groups to expand to fill vacated clinical responsibilities.Other recent research suggests that between 2012 and 2018, nearly 25% of hospitalists first identified in 2012 shifted their fulltime practice to other settings while still doing part-time hospitalist work 11. Our data on PECOS-identified hospitalists who no longer meet the 90% threshold seem to affirm that some hospitalists transition to nonhospital settings, such as skilled nursing facilities or office-based settings.…”
supporting
confidence: 57%
“…Dr Houtrow's comparison to previous studies, however, warrants a larger discussion. Unlike the University of Michigan study that was a single-center study of faculty with a low response rate (25.9%), 3 our study was conducted on a national level, focused on internal medicine residents and had a high response rate (72.5%). The study findings-12.8% of internal medicine residents self-reported experiencing sexual harassment 1 -parallel the findings of other large multisite survey-based studies with similar response rates, including 1 centered on early career development awardees and another study of surgical residents where sexual harassment was reported by 16.3% and 10.3% of respondents, respectively.…”
mentioning
confidence: 99%
“…(2) Are inpatient care models changing with this hospitalist expansion? and, most importantly, (3) Is this trend improving patient outcomes? Undoubtedly, there are several drivers of the rise in the hospitalist profession, including employment of hospitalists for co-management on specialty services, 2 expanding roles of geriatrician-hospitalists in palliative and hospice care, more parttime hospitalists, 3 work-hour reductions leading to smaller censuses on resident services, and hospital leadership's attraction to the greater revenue created by hospitalists through more high-severity billing and reduced length of stay (LOS).…”
mentioning
confidence: 99%
“…and, most importantly, (3) Is this trend improving patient outcomes? Undoubtedly, there are several drivers of the rise in the hospitalist profession, including employment of hospitalists for co-management on specialty services, 2 expanding roles of geriatrician-hospitalists in palliative and hospice care, more parttime hospitalists, 3 work-hour reductions leading to smaller censuses on resident services, and hospital leadership's attraction to the greater revenue created by hospitalists through more high-severity billing and reduced length of stay (LOS). 4,5 Perhaps one of the biggest drivers is the exodus of primary care physicians (PCPs) from inpatient rounding, a reflection of the intense demands that have grown in both hospital and ambulatory care settings.…”
mentioning
confidence: 99%